Targeting myeloid cells in pancreatic ductal adenocarcinoma: from primary tumors to liver metastasis - Gong, Ruining; Chen, Ying; Li, Chang; Zhang, Huan; Liu, Zimin; Yu, Qian (Frontiers in Immunology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the malignancies with the highest mortality rates, and outcomes are particularly poor in cases of liver metastasis. Early or recurrent metastatic PDAC significantly worsens patient outcomes and presents substantial clinical challenges. Checkpoint-based immunotherapy has largely been ineffective for most pancreatic cancer patients. This ineffectiveness is not well understood, as clinical trials often involve patients with advanced diseases, such as liver and peritoneal metastases, while most preclinical studies focus on primary tumors. Recent findings indicate that the immunosuppressive tumor microenvironment (TME) is a major obstacle to effective immunotherapy in PDAC, with the metastatic immune microenvironment differing significantly from that of primary tumors. This review explores the distinct immunosuppressive mechanisms at various stages of PDAC progression, including primary tumors, pre-metastatic niches, and metastatic sites. Myeloid cells, such as tumor-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs), play pivotal roles in shaping the TME and suppressing anti-tumor immunity. Particular focus is placed on current clinical immunotherapy strategies targeting myeloid cells, and combinations with conventional chemoradiotherapy, considering contemporary knowledge and future trends. Advancements in single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics have provided deeper insights into the molecular intricacies and diversity of PDAC, revealing potential therapeutic targets. Innovative strategies targeting myeloid cells, including CD40 agonists and CSF-1R inhibitors, are being explored to reprogram the TME and enhance the efficacy of immunotherapies.